Penilaian Kompetisi pada Tumpangsari Jagung dan Kedelai Berbagai Galur pada Jarak Tanam yang Beragam - Karyawati, Anna Satyana; Nursalim, M; Putik Blessya, Christabel (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Karyawati AS, Nursalim M, Blessya CP. 2022. Competition assessment on intercropping of maize and soybeans of various strains at various planting distances. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 544-551. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Corn and soybeans are one of the crops that are in great demand in the community, because the results are easy to manage both for food and as livestock needs. In the intercropping pattern of corn and soybeans, it is necessary to pay attention to the limited living space. Planting distances that are too narrow will cause competition for water, nutrients, and absorption of sunlight. The aimed of the research was to study the competition in various intercropping patterns of maize and various soybean lines. The research was carried out in the experimental field of Agro Techno Park (ATP) Universitas Brawijaya which is located in Jatikerto village, Kromengan, Reg. Malang, East Java. Planting materials used include soybean varieties UB1, UB2, UB3, UB4 and corn varieties R007. The results of this study indicate that the use of an intercropping pattern between soybean and corn using a one-row and two-row system gives decent results with LER and R/C ratio >1. In the two-row cropping pattern, maize is superior based on the competition ratio analysis but is more submissive in the aggressiveness analysis. From the overall treatment, the highest score was obtained in the intercropping treatment between two rows of UB4 and corn plants.